E-event planner - Mohd. Zahariman, Nur Amalina (2005)
The process of exchanging information regarding activities in university is becoming more important lately. It has become even more challenging when the campus community is demanding fast and convenient access to information. Thus, there is a need to develop a solution that provides this facility. The main purpose of this E-Event Planner is to help the academicians committees in UTM to handle their event planning processes more effectively and in an easier way. The objective of this project is to develop a well-designed, visually and functionally consistent web-based application. The problems caused by manual system have triggered the idea to develop this system. With the current manual system, the event management is not systematic enough and practically too slow in planning which causes unsuccessful event. The project solution goes through five different phases: (1) strategy, (2) requirements, (3) design, (4) development and (5) evaluation. Windows-Apache- Microsoft-PHP was utilized in developing the system. As a proof of research, the system developed goes through User Acceptance Test (UAT). The UAT measures users’ acceptance to the idea of using information and communications technology in managing event activities and functionalities of the system. The result shows that the system can help contribute to a more efficient and systematic event management.